PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMUNIKASI, KOMPENSASI FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN WARUNG MINA - Sanjaya, Kadek Edi; Supartha, I Wayan Gede (E-Jurnal Manajemen, 2015)
The issue of job satisfaction has been occurred in Warung Mina Peguyangan was bad relationship between leader and subordinate that the leader less give motivation and take attention for its subordinate. This study aims to find out the effect of transformational leadership, communication and financial compensation toward employee job satisfaction. This study was conducted at Warung Mina Peguyangan, Denpasar. Number of sample was taken 62 respondents with saturated sampling. Analysis technique has been applied that is multiple regression analysis. Based on the result of analysis the transformational leadership communication and financial compensation partially have positive and significant effect toward employee job satisfaction. Limitations in this study that are the researcher just only use three independent samples to measure work satisfaction. Next researcher should make it perfect by add other variable that have correlation with job satisfaction.
Keywords: Transformational Leadership, Communication, Financial Compensation, Job Satisfaction.